Hubungan Aktivitas Fisik dengan Dismenore Primer pada Remaja Putri: Systematic Review - Astika Gita Ningrum; Dewi Setyowati; Maria Octaviani Kartini Sema (Universitas Batanghari Jambi, 2023)
The prevalence of dysmenorrhea in adolescents worldwide ranges from 41.7% -94%. This is caused by age at menarche, genetic, BMI, diet, duration of menstrual bleeding, smoking, coffee consumption and physical activity. Physical activity produces short-term non-specific analgesics thereby reducing pain. To determine the relationship between physical activity and primary dysmenorrhea in young women. This study used a systematic review by searching the literature from four e-databases namely Pubmed, Sciencedirect, Scopus, and Web of science. The inclusion criteria in this study were articles in the last 5 years (2018-2022), English literature, full text, open access literature, originalresearch and described physical activity with the incidence of primary dysmenorrhea in adolescents, while the exclusion criteria for this study were literature originating from non-research study, adolescents with secondary dysmenorrhea. Literature quality assessment uses a quality assessment tool from EPHPP (Effective Public Health Practice Project). From the 9 (nine) articles reviewed, it was found that all articles had a relationship between physical activity and primary dysmenorrhea. Physical activity is associated with primary dysmenorrhea in female adolescents.